Application of HIRADC and JSA for Hazard Control In The Water Treatment Plant Area PT. XYZ - Hasyim Asy’ari; Siti Ernawati (Universitas Islam Raden Rahmat, Malang, 2025)
PT XYZ is a company that focuses on electricity generation, in the Water Treatment Plant (WTP) section there are activities that have a high risk to the safety and health of workers, especially in the Chemical Handling and Loading process where there are hazardous chemicals. The activity is a Chemical Loading process where the potential hazards identified include 60% chemical and 40% physical hazards. In Chemical Loading there are materials that are strong bases with a pH above 7. Therefore, the purpose of the research is to identify potential hazards at the Water Treatment Plant (WTP) and calculate risk levels according to severity (consequences) and frequency (likelihood). Using the HIRADC method aimed at company management and JSA aimed at operators. Data was obtained from interviews with 3 operators and company data. The results showed that in the process of operating the Water Treatment Plant there are 31 hazards (hazards) with 1 hazard categorized as high risk shows point 9, namely in the chemical handling & loading process which comes from corrosive chemicals that can cause burns. The control effort given is engineering in the form of providing hose clamps to prevent leakage.